2022
DOI: 10.3389/fnhum.2022.793213
|View full text |Cite
|
Sign up to set email alerts
|

Can an Online Reading Camp Teach 5-Year-Old Children to Read?

Abstract: Literacy is an essential skill. Learning to read is a requirement for becoming a self-providing human being. However, while spoken language is acquired naturally with exposure to language without explicit instruction, reading and writing need to be taught explicitly. Decades of research have shown that well-structured teaching of phonological awareness, letter knowledge, and letter-to-sound mapping is crucial in building solid foundations for the acquisition of reading. During the COVID-19 pandemic, children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Exclusion criteria included: (1) Any brain injury and medications that impact cognition; (2) Intellectual disability, Autism Spectrum Disorder, mood disorders, and other disorders that impact cognition; (3) Significant and permanent hearing impairments. After the initial screening process, 53 eligible participants were invited to take part in the follow-up study at I-LABS when they were 5-years-old ( Weiss et al, 2022 ). Among the 53 participants who participated in the follow-up study at the age of 5 years, a smaller group also completed brain imaging data collection at 26 months ( N = 20, 12 females, M = 27.34 months, SD = 0.73).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion criteria included: (1) Any brain injury and medications that impact cognition; (2) Intellectual disability, Autism Spectrum Disorder, mood disorders, and other disorders that impact cognition; (3) Significant and permanent hearing impairments. After the initial screening process, 53 eligible participants were invited to take part in the follow-up study at I-LABS when they were 5-years-old ( Weiss et al, 2022 ). Among the 53 participants who participated in the follow-up study at the age of 5 years, a smaller group also completed brain imaging data collection at 26 months ( N = 20, 12 females, M = 27.34 months, SD = 0.73).…”
Section: Methodsmentioning
confidence: 99%
“…All 53 eligible participants’ families completed an online parental questionnaire that included questions regarding children’s health and development history, language learning history, family history of dyslexia and reading difficulties, parental education, and socio-economic status (SES). Participants’ reading and related skills at the age of 5-years were measured with the following standardized and non-standardized tests that were adapted to online administration by uploading the stimuli to PowerPoint presentations and presented to the participants during online sessions via Zoom ( Weiss et al, 2022 ). The online administration of these tests was a response to the COVID-19 pandemic, when it was not possible to meet with participants in person.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Jadán-Guerrero et al (2020), using both natural materials and a digital program with children aged 5-6 who had phonological awareness issues, it was concluded that the applied program had a positive impact on the development of children's phonological awareness skills. Weiss et al (2022) prepared an online reading camp education program for five-year-old children. The research included five-year-old children from the experimental group, who participated in the online reading camp program, and the control group, who did not receive the education.…”
Section: Comparison Of the Experimental Groups With The Control Groupmentioning
confidence: 99%
“…Using digital games in the educational process; critical thinking, problem-solving, knowledge construction (Moyer et al, 2002), using digital games in the educational process; critical thinking, problem-solving, knowledge construction (Moyer et al, 2002), matching, classifying, sorting, counting and coding (Pila et al, 2019;Stephen & Plowman, 2014), cognitive skills such as discovery, creativity, as well as acting autonomously, cooperation, intrinsic motivation (Arnott, 2013;Ferrari & Addessi, 2014;Lennon et al, 2022;McClarty et al, 2012;Ryan et al, 2006;Xiong et al, 2022), it also supports phonological awareness skills, one of the early literacy skills, as well as social skills such as. Studies conducted using digital games have shown contributions to the development of subdimensions of phonological awareness, such as syllable awareness, segmentation of words into syllables (Da Silva et al, 2022;Elimelech & Aram, 2020), syllable merging, syllable deletion from words (Amorim et al, 2020), rhyme detection, and rhyme matching (Goffredo et al, 2016;Puolakanaho et al, 2003;Van Goch et al, 2017), initial sound identification, matching words with the same initial sounds, sound deletion from words, blending sounds and syllables (Arnold et al, 2021;Cameron, 2023;Li et al, 2020;Sá et al, 2022), word segmentation into sounds, and letter knowledge (Kartal & Terziyan, 2016), as well as coding skills (Weiss et al, 2022).…”
mentioning
confidence: 99%